Structural and Chemical Compatibilities of Li1−xNi0.5Co0.2Mn0.3O2 Cathode Material with Garnet‐Type Solid Electrolyte for All‐Solid‐State Batteries. Issue 46 (15th October 2021) - Hong, Seokjae; Song, Seok Hyun; Cho, Moses; Kim, Seulgi; Yu, Seung‐Ho; Lee, Dongju; Kim, Hyungsub
Abstract: All‐solid‐state batteries (ASSBs) based on ceramic materials are considered a key technology for automobiles and energy storage systems owing to their high safety and stability. However, contact issues between the electrode and solid‐electrolyte materials and undesired chemical reaction occurring at interfaces have hindered their development. Herein, the chemical compatibility and structural stability of composite mixtures of the layered cathode materials Li1− x Ni0.5 Co0.2 Mn0.3 O2 (NCM523) with the garnet‐type solid electrolyte Li6.25 Ga0.25 La3 Zr2 O12 (LLZO‐Ga) during high‐temperature co‐sintering under various gas flowing conditions are investigated. In situ high‐temperature X‐ray diffraction analysis of the composite materials reveals that Li diffusion from LLZO‐Ga to NCM523 occurs at high temperature under synthetic air atmosphere, resulting in the decomposition of LLZO‐Ga into La2 Zr2 O7 and the recovery of charged NCM523 to the as‐prepared state. The structural stability of the composite mixture at high temperature is further investigated under N2 atmosphere, revealing that Li diffuses toward the opposite direction and involves the phase transition of LLZO‐Ga from a cubic to tetragonal structure and the reduction of the NCM523 cathode to Ni metal. These findings provide insight into the structural stability of layered cathode and garnet‐type solid‐electrolyte composite materials and the design of stable interfaces between them via co‐sintering for ASSBs. Abstract : Co‐sintering is an efficient approach to solve the contact issues between electrode and solid‐electrolyte materials. However, undesired chemical reaction occurring at interface hinders their development, thus understanding the chemical compatibility of battery materials is crucial for improving interface. In this study, structural stability and chemical compatibility between layered cathode and garnet‐type solid electrolyte are explored via co‐sintering for all‐solid‐state batteries.